2018
DOI: 10.1371/journal.pone.0197336
|View full text |Cite
|
Sign up to set email alerts
|

Opportunistic osteoporosis screening via the measurement of frontal skull Hounsfield units derived from brain computed tomography images

Abstract: Background and purposeOsteoporosis is one of the most common chronic metabolic diseases, but detection and treatment rates are low. The aim of the current study was to evaluate the correlation between frontal skull Hounsfield unit (HU) values from brain computed tomography (CT) scans and T-scores of the lumbar spine and femoral neck from dual-energy X-ray absorptiometry (DXA) scans.MethodsPatients with < 1 year between brain CT and DXA scans were included in the study. The average frontal skull HU value used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 20 publications
1
16
0
1
Order By: Relevance
“…Previous studies reported that specific regional cancellous bone HU values from CT scans showed strong correlation with T-score and may be useful for predicting osteoporotic conditions [16][17][18][19]. We previously demonstrated a strong correlation between T-score and frontal skull HU value [14,20]. As osteoporosis is a systemic disease, we propose that osteoporotic conditions may influence cancellous bone structures in the skull.…”
Section: Discussionmentioning
confidence: 64%
“…Previous studies reported that specific regional cancellous bone HU values from CT scans showed strong correlation with T-score and may be useful for predicting osteoporotic conditions [16][17][18][19]. We previously demonstrated a strong correlation between T-score and frontal skull HU value [14,20]. As osteoporosis is a systemic disease, we propose that osteoporotic conditions may influence cancellous bone structures in the skull.…”
Section: Discussionmentioning
confidence: 64%
“…Previous studies have demonstrated that specific regional cancellous bone HU values from CT scans show a strong correlation with the T-score and may be useful for predicting osteoporotic conditions ( 13 15 ). We previously showed a strong correlation between the T-score and frontal skull HU values ( 7 , 16 ). Because osteoporosis is a systemic disease and is strongly related to genetic components of type 1 collagen ( COL1A1 and COL1A2) , we propose that osteoporotic conditions may influence cancellous bone of the skull ( 17 ).…”
Section: Discussionmentioning
confidence: 92%
“…Osteoporosis is a systemic disease that affects systemic bone mass and microarchitecture throughout the body. We previously reported the close association between mean frontal skull HU and BMD [8,14]. We also demonstrated that systemic osteoporosis may negatively affect the integrity of arachnoid trabeculae and granulations because bone, arachnoid trabeculae, and granulations are all composed of type 1 collagen [8,9].…”
Section: Fig 2 Comparisons Of Age Mean Frontal Skull Hu Value Gtv mentioning
confidence: 91%
“…We previously demonstrated detailed methods for measuring HU values at each of four lines on the frontal cancellous bone. This was between the right and left coronal sutures on axial CT slices at the point where the lateral ventricles disappear [8,14]. The HU value of the frontal cancellous bone was measured using the "Linear histogram graph" function in the picture archiving and communication system (PACS) (PiViewSTAR version 5.0, INFINITT Healthcare, Seoul, Korea).…”
Section: Measurement Of Frontal Skull Humentioning
confidence: 99%